Macaronesian Muscidae (Diptera). III. First record of the genus Spilogona Schnabl based on two new endemic species from the Azores and Madeira - Michelsen, Verner (Zootaxa, 2021)
The occurrence of the muscid genus Spilogona Schnabl in Macaronesia is documented for the first time by the description of two new species, S. azorensis sp. nov. and S. maderensis sp. nov. These appear to be local endemics of the Azores and Madeira, respectively.